CONSUMER LEGAL PROTECTION IN FOOD PRODUCT BRANDS: ANALYSIS OF LAW NUMBER 8 OF 1999 - Ahmad, Sufmi (SEAN Institute, 2022)
Every human being basically needs goods and/or services to fulfill their needs. Human needs are very diverse and can be distinguished into various kinds of needs. When viewed from the level, the needs of consumers can be divided into three, namely primary, secondary and tertiary needs. With the variety and various types of needs, every human being will try to meet the needs of his life in the form of goods and services. These various needs are offered by business actors so as to create a reciprocal relationship between consumers and business actors and need each other. Various kinds of goods and/or services offered by business actors to consumers as a reciprocal relationship. There is interdependence and need between consumers and business actors, so that the position of consumers and business actors should be in a balanced position. But in reality, the position of consumers and business actors is not balanced. This research is analytical descriptive, which is a research method that is carried out by describing or describing facts in the form of secondary data and primary legal materials (laws and regulations). The approach method used in this research is normative juridical, which is a method in which the law is conceptualized as responsible norms, rules, and principles. Meanwhile, the data collection technique was carried out by using a general literature study research method, examining the laws and regulations, the 1945 Constitution, Law Number 8 of 1999 concerning Consumer Protection, Law of the Republic of Indonesia Number 18 of 2012 concerning Food and Government Regulation Number 69 of 1999 concerning Food Labels and Advertisements, and the results of this study explain that, The form of legal protection carried out by the government is by making rules as regulated in Article 108 paragraph (1) of Law Number 18 of 2012 concerning Food and applying these rules effectively. consistently without discrimination, then the government supervises these rules and provides education through the socialization of regulations so that people are aware of their rights and obligations as consumers. The consumer protection law provides two kinds of space for consumer dispute resolution, namely the settlement of consumer disputes through the courts and consumer settlements out of court.